Capturing Sound: How Technology Has Changed Music - Katz, Mark (Berkeley, CA University of California Press, 2004)
There is more to sound recording than just recording sound. Far from being simply a tool for the preservation of music, the technology is a catalyst. This is the clear message of Capturing Sound, a wide-ranging, deeply informative, consistently entertaining history of recording's profound impact on the musical life of the past century, from Edison to the Internet. In a series of case studies, Mark Katz explores how recording technology has encouraged new ways of listening to music, led performers to change their practices, and allowed entirely new musical genres to come into existence. An accompanying CD, featuring thirteen tracks from Chopin to Public Enemy, allows readers to hear what Katz means when he discusses music as varied as King Oliver's "Dippermouth Blues," a Jascha Heifetz recording of a Brahms Hungarian Dance, and Fatboy Slim's "Praise You."
Keywords: 20th Century (1901-2000); Music history; Sound recording industry; Musical style